2021
DOI: 10.25179/tjem.2020-78532
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Awareness of Hypertension in Seven Distinct Geographic Regions of Turkey: The SEMT HT Study

Abstract: Objective: This study aimed to assess the prevalence, the level of awareness, and the factors that increase hypertension in Turkey. Material and Methods: A cross-sectional survey with a multi-stage probability sampling was conducted. A total of 9604 people were screened; of them, 9316 had a complete clinical examination. The ages, genders, personal and family histories of hypertension, diabetes, coronary artery diseases were recorded. Their systolic and diastolic blood pressures (BP), heights, weights, waist, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 34 publications
1
5
1
1
Order By: Relevance
“…In another study conducted in seven regions of Turkey, the prevalence of hypertension was 36.5%. In the same study, the prevalence of hypertension in the Black Sea region, where this study was carried out, was 44.9% (Bayram et al, 2021). Contrary to our research results, the prevalence of hypertension in rural areas was revealed to be higher than those living in urban areas in a recent study conducted in Turkey and research conducted in China (Bayram et al, 2021;Xing et al, 2019).…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations
“…In another study conducted in seven regions of Turkey, the prevalence of hypertension was 36.5%. In the same study, the prevalence of hypertension in the Black Sea region, where this study was carried out, was 44.9% (Bayram et al, 2021). Contrary to our research results, the prevalence of hypertension in rural areas was revealed to be higher than those living in urban areas in a recent study conducted in Turkey and research conducted in China (Bayram et al, 2021;Xing et al, 2019).…”
Section: Discussioncontrasting
confidence: 80%
“…In the same study, the prevalence of hypertension in the Black Sea region, where this study was carried out, was 44.9% (Bayram et al, 2021). Contrary to our research results, the prevalence of hypertension in rural areas was revealed to be higher than those living in urban areas in a recent study conducted in Turkey and research conducted in China (Bayram et al, 2021;Xing et al, 2019). This difference can be explained by the fact that the district where the study was conducted is close to the city center and the health education interventions for society's awareness of hypertension within the scope of the learning festival held in the district center for the last five years.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Prevalensi awareness hipertensi pada kelompok umur menunjukan perbedaan yang signifikan, umur 15-44 tahun (19,4%), umur 45-64 tahun (45,4%) dan diatas 65 tahun (52,6%) (Li et al, 2019). Penelitian di Turki menunjukan bahwa lebih dari sepertiga orang dewasa mengalami hipertensi (36,5%) dimana hanya sepertiga yang menyadari sedang menderita hipertensi (Bayram et al, 2021). Hasil survei pada daeral rural Tanzania dimana hanya sepertiga (34,3%) dari responden yang menyadari bahwa mereka hipertensi, sedangkan dua pertiga sisanya (65,7%) tidak terdiagnosis (Muhihi et al, 2020).…”
Section: Pembahasanunclassified